DNC/HNC and N2D+/N2H+ ratios in high-mass star-forming cores. Issue 1 (11th March 2014) - Fontani, F.; Sakai, T.; Furuya, K.; Sakai, N.; Aikawa, Y.; Yamamoto, S.
Abstract: Chemical models predict that the deuterated fraction (the column density ratio between a molecule containing D and its counterpart containing H) of N2 H +, D frac (N2 H + ), high in massive pre-protostellar cores, is expected to rapidly drop by an order of magnitude after the protostar birth, while that of HNC, D frac (HNC), remains constant for much longer. We tested these predictions by deriving D frac (HNC) in 22 high-mass star-forming cores divided in three different evolutionary stages, from high-mass starless core candidates (HMSCs, eight) to high-mass protostellar objects (HMPOs, seven) to ultracompact H ii regions (UCHIIs, seven). For all of them, D frac (N2 H + ) was already determined through IRAM 30 m Telescope observations, which confirmed the theoretical rapid decrease of D frac (N2 H + ) after protostar birth. Therefore, our comparative study is not affected by biases introduced by the source selection. We have found average D frac (HNC) of 0.012, 0.009 and 0.008 in HMSCs, HMPOs and UCHIIs, respectively, with no statistically significant differences among the three evolutionary groups. These findings confirm the predictions of the chemical models, and indicate that large values of D frac (N2 H + ) are more suitable than large values of D frac (HNC) to identify cores on the verge of forming high-mass stars, likewise what was found in the low-mass regime.